An Evaluation of the Accessibility of Electronic Based Government Systems for Persons with Disabilities: Case Studies in Indonesia, the Philippines, and Dubai - Abdul Majid (Journal of Governance and Administrative Reform, 2026)
Abstract The Electronic Based Government System (EBGS) in Indonesia seeks to promote more efficient, transparent, and accountable governance through the use of information and communication technology (ICT). However, its implementation continues to present significant challenges, particularly in ensuring accessibility and inclusion for persons with disabilities. This article evaluates EBGS policies in Indonesia by examining the barriers faced by persons with disabilities in accessing digital public services and comparing these issues with case studies from the Philippines and Dubai. Through comparative analysis, this article identifies best practices and proposes policy recommendations for developing an inclusive and responsive EBGS that addresses the needs of all citizens, including persons with disabilities. Keywords: electronic based government system; digital inclusion; accessibility; persons with disabilities.